PET-based classification of corticobasal syndrome. (May 2022) - Nakano, Yoshikazu; Shimada, Hitoshi; Shinotoh, Hitoshi; Hirano, Shigeki; Tagai, Kenji; Sano, Yasunori; Yamamoto, Yasuharu; Endo, Hironobu; Matsuoka, Kiwamu; Takahata, Keisuke; Kubota, Manabu; Takado, Yuhei; et al.
Abstract: Introduction: Corticobasal degeneration (CBD) is the most common neuropathological substrate for clinically diagnosed corticobasal syndrome (CBS), while identifying CBD pathology in living individuals has been challenging. This study aimed to examine the capability of positron emission tomography (PET) to detect CBD-type tau depositions and neuropathological classification of CBS. Methods: Sixteen CBS cases diagnosed by Cambridge's criteria and 12 cognitively healthy controls (HCs) underwent PET scans with 11 C-PiB, 11 C-PBB3, and 18 F-FDG, along with T1-weighted magnetic resonance imaging. Amyloid positivity was assessed by visual inspection of 11 C-PiB retentions. Tau positivity was judged by quantitative comparisons of 11 C-PBB3 binding to HCs. Results: Sixteen CBS cases consisted of two cases (13%) with amyloid and tau positivities indicative of Alzheimer's disease (AD) pathologies, 11 cases (69%) with amyloid negativity and tau positivity, and three cases (19%) with amyloid and tau negativities. Amyloid(−), tau(+) CBS cases showed increased retentions of 11 C-PBB3 in the frontoparietal areas, basal ganglia, and midbrain, and reduced metabolism in the precentral gyrus and thalamus relative to HCs. The enhanced tau probe retentions in the frontal gray and white matters partially overlapped with metabolic deficits and atrophy and correlated with Clinical Dementia Rating scores. Conclusions: PET-based classification of CBS was in accordance with previous neuropathological reports on the prevalences of AD, non-AD tauopathies, and others in CBS. The current work suggests that 11 C-PBB3-PET may assist the biological classification of CBS and understanding of links between CBD-type tau depositions and neuronal deteriorations leading to cognitive declines. Highlights: Amyloid and tau PET imaging enabled the classification of CBS into three categories. Amyloid(−), tau(+) CBS showed tau depositions in the frontoparietal cortices and subcortical structures. Tau PET signals in amyloid(−), tau(+) CBS agreed with tau pathologies in CBD and related disorders. PET-detectable tau accumulations in amyloid(−) tau(+) CBS were associated with cognitive decline. Tau PET could be an objective marker for the disease severity in CBS.